Cointegration analysis of public expenditure on tertiary education and economic growth in Nigeria - Japheth T. Torruam; Moses A. Chiawa; Cyprian C. Abur (CBN Journal of Applied Statistics, 2014)
The paper investigates the Impact of public expenditure on tertiary education and economic growth in Nigeria using time series data for the period 1990-2011The econometric methodology employed was cointegration and errorcorrection technique. The study concludes that public expenditure on tertiaryeducation has positive impact on economic growth in Nigeria. The study recommended that government and private sectors should partner by mobilizing resources to furnish tertiary institutions and equip them with adequate facilities in order to enhance tertiary education development for sustainable economic growth.
Keywords: O11; 330; Public Expenditure; Economic Growth; Cointegration; Development